Design and construction of compact electromagnetic undulator for THz radiation production - Thongbai C. (2017)
Copyright © 2016 CC-BY-3.0 and by the respective authors. The goal of this research is to design and construct a compact electromagnetic undulator. This insertion device will be installed at the PBP-CMU-LINAC system of Chiang Mai University (CMU), Thailand, to produce THz radiation. The undulator magnet is designed by using 2D POISSON and 3D RADIA computer code to optimize the magnet dimensions. The width of iron pole (W) should be 12 mm. The length of iron pole (L) should be about 80 mm long and the thickness of return yoke (d) should be more than 10 mm. The magnet design, the in-house construction of the magnet, and the measurement results will be presented.